Fish community shifts along a strong fluvial environmental gradient revealed by eDNA metabarcoding. Issue 1 (1st June 2021) - García‐Machado, Erik; Laporte, Martin; Normandeau, Eric; Hernández, Cecilia; Côté, Guillaume; Paradis, Yves; Mingelbier, Marc; Bernatchez, Louis
Abstract: Large rivers and their estuaries are structurally complex and comprise a diversity of habitats supporting a rich biodiversity. As a result, identifying and monitoring fish communities using traditional methods in such systems may often be logistically challenging. Using the mitochondrial DNA 12S MiFish primers, we performed an eDNA metabarcoding analysis to assess the effect of spatial and environmental factors on the variation of the fish community structure along most of the St. Lawrence River/Estuary/Gulf (Québec Canada), a transect spanning 1300 km across a diversity of habitats from a fluviatile non‐tidal section to a marine environment. A total of 129 species were identified including freshwater and marine species. For the freshwater sectors, eDNA identified 80 species compared with the 85 species previously reported based on conventional sampling. eDNA also revealed similar species diversity and communities in the fluviatile section of the St. Lawrence River. Furthermore, our study improved current knowledge about the brackish and marine sections by describing community transition between freshwater and marine fish communities in association with a drastic shift in environmental conditions observed between the end of the fluvial estuary and the beginning of the middle (brackish) estuary. Altogether, this study exemplifies how eDNA metabarcoding is a powerful tool to document fish community shifts in large temperate lotic ecosystems. Abstract : eDNA metabarcoding efficiently identified the vast majority of fish species of the St. Lawrence River /Estuary/Gulf (Quebec Canada). eDNA metabarcoding identified a pattern of fish communities differentiation strongly associated with a series of longitudinal hydro‐morphological structures and to the upstream–downstream effect of a gradient of salinity, temperature, and tide height variations.